1986
DOI: 10.1104/pp.82.3.867
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gravity on the Formation of Amyloplasts in Columella Cells of Zea mays L

Abstract: MATERIALS AND METHODSFlight Hardware. Flight hardware consisted of four concentrically sealed bags of heat-sealable Kapak plastic (Fisher Scientific, Springfield, NJ). The innermost bag measured approximately 10 x 10 cm and contained approximately 100 ml of 2% (v/v) glutaraldehyde in 0.05 M sodium cacodylate buffer (pH 6.9). This 'fixative bag' was placed inside a 'growth chamber' bag measuring approximately 25 x 30 cm containing the plant material (see below) and inflated to near capacity with air. This bag w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…There are several pieces of evidence that O -acetylation of wall polysaccharides in plants occurs in the endomembrane system, most likely the Golgi apparatus, where non-cellulosic polysaccharides are synthesized (Moore et al, 1986; Scheible and Pauly, 2004). First, O -acetylated XyG can be isolated from intact microsomes of Arabidopsis confirming that O -acetylation occurs prior to deposition of the wall polysaccharide in the apoplast (Obel et al, 2009).…”
Section: Mechanisms Of Cell Wall Polymer O-acetylation: Comparison Tomentioning
confidence: 99%
“…There are several pieces of evidence that O -acetylation of wall polysaccharides in plants occurs in the endomembrane system, most likely the Golgi apparatus, where non-cellulosic polysaccharides are synthesized (Moore et al, 1986; Scheible and Pauly, 2004). First, O -acetylated XyG can be isolated from intact microsomes of Arabidopsis confirming that O -acetylation occurs prior to deposition of the wall polysaccharide in the apoplast (Obel et al, 2009).…”
Section: Mechanisms Of Cell Wall Polymer O-acetylation: Comparison Tomentioning
confidence: 99%
“…Quantitative immunolabeling experiments using antibodies recognizing either the XyG backbone (anti-XG antibodies: Moore et al, 1986; Lynch and Staehelin, 1992) or an α- l -Fuc p -(1-2)-β- d -Gal p epitope of XyG side chains in sycamore cultured cells have shown that the epitopes localize to trans cisternae and the TGN (Zhang and Staehelin, 1992). These data suggested that the synthesis of XyG occurs exclusively in late compartments of the Golgi and that no precursor forms of XyG are made in cis and medial cisternae.…”
Section: The Role Of the Golgi Apparatus In Complex Polysaccharide Bimentioning
confidence: 99%
“…To analyse the ultrastructural organisation of plasmodesmata during tissue 129 differentiation, we first focused on Arabidopsis root tip columella (COL), a tissue 130 involved in gravitropism and soil excavation [41][42][43] . COL cells offered excellent 131 plasmodesmata preservation after cryo-fixation and freeze-subtitution but also 132 unequivocal traceability of cell lineage where plasmodesmata modification from early 133 formation to later maturation stages can be easily traced.…”
Section: Er-pm Spacing Within Plasmodesmata Is Regulated During Tissumentioning
confidence: 99%